(untitled) (Contemporary Journal of Social Science Review, 2025)
Dr. Hafeez Ahmed is a important personality of Punjabi Literature. He is a Poet, Prose Writer and a Researcher but his strong reference is Punjabi Naat. He has introduced new trends in Naat. He wrote Naat in form of Folk Generes like Mahiya, Tappa etc. He also wrote Naatia Dewan and he used one alphabet as a Radeef in the whole book. This research paper explores his poetic treatment in Naat. Dr. Hafeez used different allusions and other devices to describe Seerat-ul-Nabbi (SAW). In this paper an attempt has been made to introduce Dr. Hafeez’s personality, his books. This paper focuses on the thematic and artistic analysis of his Naat and researchers has tried to describe the aspects of Naat of Dr. Hafeez with suitable examples from the text.